Special Diophantine Quadruple for Gnomonic Number with D (2) - Janaki , G.; Sarulatha , R. (Explorations in Diophantine Equations, 2023)
This paper aims in creating a sequence of special Dio 4-tuple with the property for gnomonic number with consecutive ranks such that for any two tuples in the set product of the number added with their sum and increased by two is a perfect square and some numerical illustrations are also presented.